Implementasi Komunikasi Data Berbasis ZigBee pada SCADA (Supervisory Control and Data Acquisition) PLTMh - Beny Firman; Suharyanto; Eka Firmansyah (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
Recently, Microhydro Power Center (Pusat Listrik Tenaga Mikrohidro or PLTMh) has been spread widely the energy electric generator. PLTMh control system in Indonesia often uses automatic control system. One of the reasons for this is that the operation and monitoring of the PLTMh could be done from a distance. One of PLTMh models of remote control is known as SCADA. One of the main parts of SCADA is Master Station (MS), Remote Terminal Unit (RTU) & Communication System. Communication System in SCADA can be built in several choices: wired or wireless. Remote control can be built using Wireless Sensor Network (WSN) system. The application of WSN in operating SCADA could ease installation and increase communication reliability. This study applied ZigBee technology on PLTMh SCADA control data communication. ZigBee was chosen because it’s free of operation and licensing charge, had OSI feature and low cost, those are reasons why they are best suited to PLTMh application. In the application, ZigBee hardware was divided into several parts: Coordinator on Master Station(MS) (one unit), End Devices which were each RTU unit point (two units) and Router as a data hooping between Coordinator & End Device (one unit). The furthest point between Coordinator and End Device through Router could reach 645 meters. This was tested in LOS (Line of Sight) condition. RSSI signal on ZigBee was used to see the strength of signal reception on Coordinator as data collector. RSSI score (-dBm) became smaller at maximum distance variation. This meant signal power at data jump point became lower. ZigBee based data communication to form SCADA network had been built well in join a network model, which was between Coordinator — Router — End Device at the furthest distance, 645 meters, with signal power of -82dBm.